Reframing Islamic Education Management through the Lens of Maqāṣid al-Sharīʿah: Evidence from Madrasah Education - Fitroh Muspiatu Sangadah; Feri Riski Dinata (KURAS Institute, 2025)
The contemporary educational landscape necessitates continuous innovation in management systems while remaining firmly grounded in Islamic sharīʿah values. This condition underscores the importance of integrating the modernization of educational management with normative religious principles. In response to this phenomenon, the present study seeks to examine how the transformation of educational management can be implemented from the perspective of Maqāṣid al-Sharīʿah. This research aims to analyze the process through which educational management undergoes transformation. Employing a qualitative approach with a field study design, data were collected through interviews, observations, and document analysis. The data were analyzed through several stages, namely data reduction, data display, and the drawing of conclusions. The findings, based on field data obtained from interviews with the head of the madrasah, indicate that the implementation of Maqāṣid al-Sharīʿah plays a crucial role in institutional development and serves as a catalyst for meaningful change. This study contributes by offering a novel perspective that integrates Maqāṣid al-Sharīʿah values with educational management practices. The study concludes that such an approach not only enhances institutional efficiency and innovation but also fosters an educational system oriented toward achieving a balance between worldly and spiritual objectives.